1985
DOI: 10.1080/00048678509158842
|View full text |Cite
|
Sign up to set email alerts
|

Social Skills Training: An Effective Treatment for Unipolar Non-Psychotic Depression?

Abstract: In recent times, social skills training (SST) has been used in the treatment of unipolar non-psychotic depression. We outline the rationale for SST in such treatment, provide definitions of SST, and outline the assessment and training procedures. Published studies are reviewed and their shortcomings discussed. We examine four theoretical issues arising from the review, and guidelines for improvements in future studies are suggested.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 38 publications
0
7
0
2
Order By: Relevance
“…Overall, studies comparing the efficacy of assertiveness training to other evidence-based treatments have found that although assertiveness training is generally effective in increasing assertive behaviors and decreasing depressive symptoms, its efficacy is essentially equivalent to other forms of treatment for depression (Rehm, Fuchs, Roth, Kornblith, & Romano, 1979;Rude, 1986;Zeiss, Lewinsohn, & Muñoz, 1979). Two meta-analyses of past research comparing psychotherapy outcomes for depression in adults (Barth et al, 2013;Cuijpers et al, 2008) and a review of the social skills literature (Jackson, Moss, & Solinski, 1985) have come to largely the same conclusion, finding that social skills training, which primarily involved assertiveness training, was more effective than wait-list control and largely no different in effectiveness compared to other psychotherapeutic interventions, such as cognitive therapy or behavioral activation. An important issue that was indicated from these meta-analyses and the reviews that have been conducted on the efficacy of assertiveness training for depression is the paucity of empirical studies relative to other evidence-based treatments (Heimberg et al, 1977).…”
Section: Depressionmentioning
confidence: 99%
“…Overall, studies comparing the efficacy of assertiveness training to other evidence-based treatments have found that although assertiveness training is generally effective in increasing assertive behaviors and decreasing depressive symptoms, its efficacy is essentially equivalent to other forms of treatment for depression (Rehm, Fuchs, Roth, Kornblith, & Romano, 1979;Rude, 1986;Zeiss, Lewinsohn, & Muñoz, 1979). Two meta-analyses of past research comparing psychotherapy outcomes for depression in adults (Barth et al, 2013;Cuijpers et al, 2008) and a review of the social skills literature (Jackson, Moss, & Solinski, 1985) have come to largely the same conclusion, finding that social skills training, which primarily involved assertiveness training, was more effective than wait-list control and largely no different in effectiveness compared to other psychotherapeutic interventions, such as cognitive therapy or behavioral activation. An important issue that was indicated from these meta-analyses and the reviews that have been conducted on the efficacy of assertiveness training for depression is the paucity of empirical studies relative to other evidence-based treatments (Heimberg et al, 1977).…”
Section: Depressionmentioning
confidence: 99%
“…The social skills training model (SST) proposes that depressed people may have difficulty initiating, maintaining and ending conversations (Jackson 1985). Because of these deficits, the individual is unable to elicit mutually reinforcing behaviour from other people in their environment.…”
Section: Methodsmentioning
confidence: 99%
“…SST subsumes assertion and conversational skills, together with more specialised subskills such as dating and job interview skills. Four social contexts of interacting with strangers, friends, family members and people at work or school are targeted (Bellack 1980) and interventions such as instruction, modelling, rehearsal, feedback and reinforcement are used to enable the development of new responses (Jackson 1985).…”
Section: Methodsmentioning
confidence: 99%
“…The social skills training model proposes that depressed people may have difficulty initiating, maintaining and ending conversations (Jackson 1985). Because of these deficits, the individual is unable to elicit mutually reinforcing behaviour from other people in his or her environment.…”
Section: Social Skills Training/assertiveness Trainingmentioning
confidence: 99%
“…Social skills training subsumes assertion and conversational skills, together with more specialised subskills, such as dating and job interview skills. Different social contexts may be targeted, for example interaction with friends, family members, people at school, or at work, and interventions such as instruction, modelling, rehearsal, feedback and reinforcement are used to enable the development of new responses (Jackson 1985). As assertiveness training represents a key component of social skills training, we included it in this category.…”
Section: Social Skills Training/assertiveness Trainingmentioning
confidence: 99%